Female Masculinity in Radclyffe Hall’s Novel The Well of Loneliness - Subedi, Shankar (Molung Educational Frontier, 2020)
This paper aims to analyze Radclyffe Hall's novel The Well of Loneliness from the perspective of female masculinity. For that purpose, it uses the concept of female masculinity developed by Judith Halberstam. Seen from the angle of female masculinity forwarded by Habersham, the present paper comes to the conclusion that masculinity falls into crisis as we compare it to how it was defined and understood traditionally. Most of the female characters in the novel show boldness, strength and ability to face and tackle different situations filled with danger and hopelessness. A young woman named Stephen Gordon pursues her passions and embarks on her own subjective world. Her activities and choices are anomalous to the established mores concerning the role and position of women. This is what goes against the conventional paradigm of gender and supports the idea of subversive female masculinity.